2018
DOI: 10.1007/s11207-018-1333-2
|View full text |Cite
|
Sign up to set email alerts
|

LOFAR Observations of Fine Spectral Structure Dynamics in Type IIIb Radio Bursts

Abstract: Solar radio emission features a large number of fine structures demonstrating great variability in frequency and time. We present spatially resolved spectral radio observations of type IIIb bursts in the 30 − 80 MHz range made by the Low Frequency Array (LOFAR). The bursts show well-defined fine frequency structuring called "stria" bursts. The spatial characteristics of the stria sources are determined by the propagation effects of radio waves; their movement and expansion speeds are in the range of (0.1−0.6)c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 35 publications
8
57
0
Order By: Relevance
“…Turbulent density fluctuations which have a power that is weaker in the parallel direction compared to the perpendicular to radial direction result in a reduced time-broadening effect (i.e. radio-wave cloud broadening along the z direction); consequently the results with anisotropy factor α = 0.3 give a characteristic decay time ∼ 0.6 s, exactly as observed (see Figure 4 in Sharykin et al 2018).…”
Section: Simulation Results For a Single Frequencysupporting
confidence: 68%
See 1 more Smart Citation
“…Turbulent density fluctuations which have a power that is weaker in the parallel direction compared to the perpendicular to radial direction result in a reduced time-broadening effect (i.e. radio-wave cloud broadening along the z direction); consequently the results with anisotropy factor α = 0.3 give a characteristic decay time ∼ 0.6 s, exactly as observed (see Figure 4 in Sharykin et al 2018).…”
Section: Simulation Results For a Single Frequencysupporting
confidence: 68%
“…Sub-arcminute imaging observations of Type III solar radio bursts have shown that intrinsic sources with sizes ∼ < 0 ′ .1 result in observed sources as large as ∼ 20 ′ at 30 MHz (Kontar et al 2017;Sharykin et al 2018), demonstrating that scattering dominates the properties of observed source sizes. Moreover, the locations of the upper and lower sub-band sources of Type II solar radio bursts are observed to be spatially separated (e.g., Zimovets et al 2012;Chrysaphi et al 2018), with the amount of separation being consistent with radio-wave scattering of plasma radio emission from a single region (Chrysaphi et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With previous imaging, the spectral resolution was too sporadic to have multiple images of one stria. A number of studies using LOFAR imaging spectroscopy (Kontar et al, 2017;Chen X. et al, 2018;Kolotkov et al, 2018;Sharykin et al, 2018) have analyzed striae bursts, concentrating on one specific event on the 16 April 2015.…”
Section: Fine Structurementioning
confidence: 99%
“…A characteristic spatial scale of striae was estimated around 700 km, using the Newkirk density model (Newkirk, 1961) rather than spatial positions because the source was located over the solar disc. Sharykin et al (2018) extended this study to analyse the spatial motion of the individual striae. These structures have an instantaneous bandwidth around 20-100 kHz that increases with increasing central frequency.…”
Section: Fine Structurementioning
confidence: 99%
“…Such high speeds are likely to be associated with apparent motion of the scattered image rather than the actual motion of the emitter (cf. Kontar et al 2017;Sharykin et al 2018).…”
Section: Dynamics Of the Emission Sourcesmentioning
confidence: 99%